HIV infection prevalence and VDRL postivity prevalence in pregnant women - Ramos, Mauro Cunha; Curcio, Beatriz Leônidas; Tessaro, Madalena; Meneghetti, Helena; Marques, Lucia Cogo; Duarte, Thiago Pereira; Cestari, Tania Ferreira (Brazilian Journal of Sexually Transmitted Diseases, 2022)
Objective: To esteem the seropositivity of VDRL and the prevaJence of HIV infection in pregnant women at the delivery room. The hospital is public and is pari of the sentinel surveillance system implemented by the National Program of STD / Aids of the Ministry of Health. This is an anonymous, unlinked surveillance system created in order to estimate the prevalence of HIV in different sentinel populations. The authors also obtained data on VDRL seropositivity in the study. Methods: A confidential and linked crosssectional study with pre and posttest counseling. A consecutive sampling was used. Ali the patients that search for delivery care during two twenty day periods in March of 1997 and April of 1988. ln the second period, an infor-med consent was obtained for performing HIV testing and a questionnaire was applied. Resulta: Of the 200 samples tested by the VORL in March of 1997, seven resulted reagents (3,5%-IC (95%) 1 .42 - 7.09). ln April of 1998, also among 200 samples, three were reagent for the VDRL (1,5% IC (95%t 0,31-4,68). During this second sampling period, of the 200 HIV tests performed, 3 resulted reagent. ( 1,5% -IC (95%) 0,3 1-4,68). Ninety women (45%) had less than 6 pre-natal care visits. HIV testing was offered to 103 of the women (55,4%). During the study, after pre-testing counseling, ali 200 women agreed of being HIV tested. Concluaiona: The results confirm that both infection are prevalent in the state of Rio Grande do Sul. They also show the necessity of reinforcing the prevention and treatment programs for congenital syphilis as we as early diagnosing of HIV infection among pregnant women and implementing prevention of vertical transmission. Attention sh ould be paid in order to reach ali the health care system (gynecology, pre-natal, delivery and mother and child care services).